2022
DOI: 10.3390/ani12101300
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Induces Shifts in the Rumen Bacteria and Metabolome of Buffalo

Abstract: Exposure to the stress (HS) negatively affects physiology, performance, reproduction and welfare of buffalo. However, the mechanisms by which HS negatively affects rumen bacteria and its associated metabolism in buffalo are not well known yet. This study aimed to gain insight into the adaption of bacteria and the complexity of the metabolome in the rumen of six buffalo during HS using 16S rDNA and gas chromatography metabolomics analyses. HS increased respiratory rate (p < 0.05) and skin temperature (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Shenhe et al [ 42 ] also examined the RR in the Mediterranean breed (MB) and a crossbreed (CB, Nili-ravi × Murrah) during the summer and observed that the MB is less tolerant to HS than the CB (76.84 ± 4.31 breaths/min vs. 60.82 ± 5.45 breaths/min, respectively). Wang et al [ 46 ] found similar values for RR during the HS period but also a high RR during the non-HS period. The respiration rate peak, shown as a panting mechanism, corresponds to the incapacity of the buffalo to dissipate heat during the HS period.…”
Section: The Effect Of Heat Stress On Buffalomentioning
confidence: 84%
See 1 more Smart Citation
“…Shenhe et al [ 42 ] also examined the RR in the Mediterranean breed (MB) and a crossbreed (CB, Nili-ravi × Murrah) during the summer and observed that the MB is less tolerant to HS than the CB (76.84 ± 4.31 breaths/min vs. 60.82 ± 5.45 breaths/min, respectively). Wang et al [ 46 ] found similar values for RR during the HS period but also a high RR during the non-HS period. The respiration rate peak, shown as a panting mechanism, corresponds to the incapacity of the buffalo to dissipate heat during the HS period.…”
Section: The Effect Of Heat Stress On Buffalomentioning
confidence: 84%
“…All of the references [ 27 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] agree that there was an increase in RR with the increase in THI. This result could be due to the increase in oxygen demand from the tissues under stressful conditions to try to maintain homeothermy by dissipating heat.…”
Section: The Effect Of Heat Stress On Buffalomentioning
confidence: 94%
“…Among the microorganisms (archaea, fungi, protozoa and bacteria) in the rumen of the buffalo under heat stress, the most changes were seen in bacteria. While heat stress did not have a significant effect on the alpha diversity of rumen bacteria, visible changes in the β-diversity of the bacterial community were detected (Wang et al, 2022).…”
Section: Effect On Rumen Metabolism Of Climate Change 411 Cattlementioning
confidence: 79%
“…Among the above formulae, THI 1 , THI 3 , and THI 6 are used to monitor discomfort from temperature and relative humidity in humans while THI 2 and THI 7 are used to investigate heat stress effects for cattle exposed in climatic chambers. Only THI 5 is used to determine the level of heat stress in dairy cattle reared outdoor (Bohmanova et al, 2007) with T db and RH representing dry bulb temperature ( o C), and relative humidity (%), respectively (Wang et al, 2022). Formulae used to calculate other environmental parameters (THI, adjusted temperature humidity index (THI), heat load index (HLI), equivalent temperature index (ETI), environment stress index (ESI), comprehensive climate index (CCI), relative humidity, wind speed, solar radiation and predicted globe temperature) are presented in Table 2, as reported in the study by Hammami et al (2013).…”
Section: Temperature-humidity Indexmentioning
confidence: 99%
“…It has been developed as a climate index to determine and reduce losses associated to heat stress (Bohmanova et al, 2007). In dairy cattle, THI that exceeds a particular threshold for cattle, often leads to significant declines in feed intake, extreme water consumption, alteration in milk yield traits, and lowered fertility (Gálik et al, 2021;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%